Representasi Makna Kesetiaan Pada Film Hachiko 2023 - Jaelani, Deden (Buana Komunikasi (Jurnal Penelitian dan Studi Ilmu Komunikasi), 2024)
In the 2023 film Hachiko, emotions are stirred by the devotion of a dog named Ba Tong to Mr. Chen. The story of animal and human loyalty is told in the 2023 Chinese film Hachiko, which is an adaptation of the original Japanese film. Based on this phenomenon, a qualitative descriptive study approach was used to find out how the semiotic analysis of the film Hachiko 2023 is seen from the meaning of denotation, connotation and myth in the film. This research uses the theory of Roland Barthes (1915–1980) which divides semiotics into two categories, namely denotation and connotation. Barthes also utilized this theory to analyze myths. The findings of this research, which include definitions of denotation, connotation, and myth, evaluate the loyalty that fellow living beings such as Tuan Chen and Ba Tong have.